2002
DOI: 10.1080/15216540214311
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Protein Hydrophobic Exposure on the Slope of the Line in the Δπ vs πi Plot

Abstract: SummaryThe ∆π vs π i curve from monolayer surface pressure detection is a powerful method to characterize the membrane insertion. The ∆π vs π i curve is fixed by two parameters, the π c and the slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The biphasic behavior can be described by the following equation with all parameters labeled in Figure 5B: ΔΠ={normalk1(normalΠnormalmnormalΠnormali)(normalΠnormali<normalΠnormalt)normalk2(normalΠnormalcnormalΠnormali)(normalΠnormalinormalΠnormals)(normalΠnormali>normalΠnormalt),where k 1 is a coefficient of phase I insertion that depends on the packing geometry of DrrA at the air-water interface (Zhang et al, 2002); k 2 is a phase II insertion coefficient with a unit of (mN/m) −1 and values ranging from 0.01 to 0.03, depending on both the binding affinity and the mechanical work done by DrrA; Π t is the transition surface pressure between phase I and II; Π m is the maximum penetration pressure of phase I insertion; Π c is the critical surface pressure of the system; and Π s is the extrapolated surface pressure threshold at which the phase II insertion starts to occur. A value of Π s smaller than Π t suggests that the insertion mode in phase II happens before the Π t is met, although below Π t it cannot be distinguished from the other insertion mode at Π i < Π t .…”
Section: Resultsmentioning
confidence: 99%
“…The biphasic behavior can be described by the following equation with all parameters labeled in Figure 5B: ΔΠ={normalk1(normalΠnormalmnormalΠnormali)(normalΠnormali<normalΠnormalt)normalk2(normalΠnormalcnormalΠnormali)(normalΠnormalinormalΠnormals)(normalΠnormali>normalΠnormalt),where k 1 is a coefficient of phase I insertion that depends on the packing geometry of DrrA at the air-water interface (Zhang et al, 2002); k 2 is a phase II insertion coefficient with a unit of (mN/m) −1 and values ranging from 0.01 to 0.03, depending on both the binding affinity and the mechanical work done by DrrA; Π t is the transition surface pressure between phase I and II; Π m is the maximum penetration pressure of phase I insertion; Π c is the critical surface pressure of the system; and Π s is the extrapolated surface pressure threshold at which the phase II insertion starts to occur. A value of Π s smaller than Π t suggests that the insertion mode in phase II happens before the Π t is met, although below Π t it cannot be distinguished from the other insertion mode at Π i < Π t .…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the antigenicity of trichosanthin as a drug while preserving its biological activity, Chan et al constructed a mini-trichosanthin (C7) by deleting 7 C-terminal amino acid residues (27), which showed mild reduced toxicity towards sensitive cells. Our previous studies indicated that C7 could also interact with a negatively charged lipid monolayer, whereas its pH-dependent membrane insertion ability was reduced (28,29). Here the interaction of C7 with a phospholipid bilayer was investigated further in order to understand the function of the C-terminus in TCS membrane insertion.…”
Section: Introductionmentioning
confidence: 98%
“…Our previous studies indicated that C7 could also interact with a negatively charged lipid monolayer, whereas its pH-dependent membrane insertion ability was reduced (28,29). Here the interaction of C7 with a phospholipid bilayer was investigated further in order to understand the function of the C-terminus in TCS membrane insertion.…”
Section: Introductionmentioning
confidence: 99%